Antibacterial Effect of Juglans Regia Bark against Oral Pathologic Bacteria - Faramarz Zakavi; Leila Golpasand Hagh; Arash Daraeighadikolaei; Ahmad Farajzadeh Sheikh; Arsham Daraeighadikolaei; Zahra Leilavi Shooshtari (International Journal of Dentistry)
Background. In this study antimicrobial effect of ethanolic and aqueous extracts of Juglans regia bark in Iran was evaluated on four different oral bacteria, Streptococcus mutans, Streptococcus salivarius, Streptococcus sanguis, and Staphylococcus aureus. Methods. Aqueous and ethanol extracts of Juglans regia bark were prepared by using disk diffusion technique and Minimal Inhibitory Concentration (MIC) methods. Tetracycline 30 μg and Erythromycin 15 μg were used as positive control and water as negative control in disk diffusion and MIC methods. Data were analyzed by ANOVA test. Results. The results showed that S. sanguis and S. mutans were the most sensitive and the most resistant bacteria against ethanolic and aqueous extracts, respectively. Ethanolic extract had significant antibacterial effect against all tested bacteria. Aqueous extract did not show antibacterial effect on S. mutans, in contrast to ethanolic extract. Aqueous extract had significantly antibacterial effect against Staphylococcus aureus, S. salivarius, and S. sanguis compared to control (P<0.0001), but it did not show effect on S. mutans when compared with Erythromycin. According to the obtained MIC values, ethanol extract of Juglans regia bark had the lowest rate. Conclusion. The results may provide the basis for using natural antimicrobial substance for oral hygiene prophylaxis purposes.